KOMPARASI MODEL PROBLEM BASED LEARNING (PBL) DAN MODEL PROJECT BASED LEARNING (PJBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Muttakin, Muttakin; Attahara, Thalitha; Dewi, Ucia Mahya (Lantanida Journal, 2024)
The PBL and PjBL models are student-centric learning models that are needed to improve student skills in the 21st century. This study aims to find out the differences between the PBL and PjBL models of critical thinking skills of students at SMAN 1 Lhokseumawe on material reaction speed. This research uses experimental methods with a type of Quasi Experimental Design. The sampling technique was carried out in a purposive way with a total sample of 72 students. The test results show no significant differences between PBL and PjBL models. The result of this test is sig (2-tailed) 0.162 > 0.05 H0 received and H1 rejected. In other words, there is no significant difference in critical thinking skills between students taught with the PjBL model and the PBL model